Formulation and Antibacterial Activity of Coffee Ground Waste Extract Face Serum - Ikhsan, Arif Nur; Suryani, Hani Nabila; Ernawati, Anik Sri; Chang, Celine Aurellia; Purwanto, Purwanto Purwanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Coffee is one of the most popular beverages around the World, which generates over million tons of coffee ground waste each year. Using technologies, the waste can be converted into value-added products such as cosmetic. The objective from this study is to formulate the coffee ground waste extract to face serum for anti-acne treatment. Samples are collected from several coffee shops, then macerated using ethanol. Formulation consisting: HPMC, tween 80, glycerin, PEG 400, sodium EDTA, sodium benzoate and triethanolamine. Evaluation is conducted to the extract antibacterial activity, face serum bacterial activity and face serum stability. The extract exhibits 0.860 gram/mL MIC50 Cutibacterium acnes, meanwhile, the face serum provides 15.30 ± 4.03 mm inhibition zone. Ultimately, the face serum is stable after 4 weeks testing using accelerated stability test in terms of organoleptic, pH and viscosity.